ASSESSING STUDENTS AND GRADUATES SOFT SKILLS, HARD SKILLS AND COMPETITIVENESS - Hadiyanto, .; Noferdiman, .; Moehamin, .; Yuliusman, . (PEOPLE: International Journal of Social Sciences, 2017)
Directorate General of Indonesians Higher Education recommended that universities graduates obtained standard core competencies. However, Universitas Jambi has not yet developed an instrument to measure students’ core competencies. Due to the fact, one of aims this project is to develop students and graduates assessment rubric of soft skills, hard skills and competiveness (SHC). Qualitative content analysis on literature review, existing instrument and transcription of FGD was conducted to reduced indicators of SHC. Content validity was obtained through workshop among the educators, while consistency of the instrument was tested by Cohen Kappa test agreement. The result of the SHC assessment rubric was specified as follows: Component of soft skills were classified into six communication skills; IT skills, Numeric Skills, Learning Skills, problem solving skills and working with others. Hard skill was not classified into smaller component but directly into indicators, while competiveness classified into three components; entrepreneurship, lifelong learning and employability. Try-out had been conducted to 21 students, and yielded acceptable to moderate level of agreement Kappa value. The result of the students’ SHC performance at pilot study shows that students’ SHC Performance in overall was at medium level. Students’ SHC level of softs skills, hard Skill and competitiveness were at medium level. For the future research, the SHC rubric assessment will be used in experimental research class on students SHC Development at four faculties; science and technology, humanities, economics and husbandry faculty at Universitas Jambi.